Thermal Efficiency Retrofit of Residential Buildings: The German Experience - Karsten Neuhoff; Hermann Amecke; Aleksandra Novikova; Kateryna Stelmakh (Climate Policy Initiative, 2011)
The German government has committed to reducing the primary energy demand of buildings by 80% by 2050. Achieving this reduction will require foremost efficiency improvements, with a first milestone of a 20% reduction in heat demand levels by 2020. Given that about 80% of today's building stock will remain in place beyond 2050, thermal retrofit of this existing building stock is essential (Figure 1). At the current rate of retrofit, however, only a fraction of the required reduction in thermal energy demand will be reached by 2050. Therefore, both scale and depth of retrofit need to be increased: The rate at which outer walls are being thermally retrofitted in Germany is currently ca. 0.8% per year for residential buildings; the government target for thermal retrofits is 2% [11]. Reaching this target will be more cost effective if thermal retrofits are linked to general, non-thermal retrofits that buildings owners pursue for non-energy related reasons (e.g. the current non-thermal retrofit rate, hence the retrofit rate that does not include energy efficiency improvements, for outside walls is 2.4%) [11]. The depth of thermal retrofits today varies significantly, ranging from single measures delivering small overall improvements to deep comprehensive retrofits that may exceed the performance of new builds by up to 50%. Since a 2% retrofit rate only allows for each building to be retrofitted once before 2050, the overall efficiency improvement can only be achieved if all thermal retrofits are deep.
Keywords: H31; Q48; R38; 330; energy efficiency; thermal retrofit; residential buildings; Energy efficient building; Residential real estate